2011
DOI: 10.1037/a0024515
|View full text |Cite
|
Sign up to set email alerts
|

Phonological effects in handwriting production: Evidence from the implicit priming paradigm.

Abstract: In the present article, we report 3 experiments using the odd-man-out variant of the implicit priming paradigm, aimed at determining the role played by phonological information during the handwriting process. Participants were asked to write a small set of words learned in response to prompts. Within each block, response words could share initial segments (constant homogeneous) or not (heterogeneous). Also, 2 variable homogeneous blocks were created by including a response word that did not share orthographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 32 publications
1
33
1
2
Order By: Relevance
“…Hence, implicit priming exclusively depended on whether word-initial graphemes were shared, but word-initial phonemic overlap was not sufficient to generate priming. These results directly contradict those reported by Afonso and Álvarez (2011), and it is of yet unclear why this is the case. Shen et al (2013) took care, however, not to interpret their findings as evidence against the involvement of phonological codes in handwritten word production.…”
contrasting
confidence: 84%
See 2 more Smart Citations
“…Hence, implicit priming exclusively depended on whether word-initial graphemes were shared, but word-initial phonemic overlap was not sufficient to generate priming. These results directly contradict those reported by Afonso and Álvarez (2011), and it is of yet unclear why this is the case. Shen et al (2013) took care, however, not to interpret their findings as evidence against the involvement of phonological codes in handwritten word production.…”
contrasting
confidence: 84%
“…The basic finding, replicated in numerous studies, is that phonological word-initial overlap leads to a facilitation effect (Meyer, 1990(Meyer, , 1991 which is attributed to partial phonological planning possible in the homogeneous but not in the heterogeneous context. Afonso and Álvarez (2011) modified this technique to require written rather than spoken responses, and reported a similar facilitation effect with Spanish participants when responses overlapped in their word-initial properties (e.g. baladabaraja-banana-basura).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Recent studies have shown that sublexical information mediates several types of writing tasks (Afonso & Álvarez, 2011;Bonin, Peereman, & Fayol, 2001;Delattre, Bonin, & Barry, 2006;Qu, Damian, Zhang, & Zhu, 2011), and theoretical models have been proposed to describe the relative involvement of the lexical and the sublexical route during spelling to dictation (Tainturier & Rapp, 2001; see also Folk & Rapp, 2004;Folk, Rapp, & Goldrick, 2002;Rapp, Epstein, & Tainturier, 2002) and/or written picture naming (Bonin et al, 2001;Roux & Bonin, 2012). However, the involvement of sublexical correspondences during copying has been investigated less than in other writing tasks.…”
mentioning
confidence: 99%
“…Over the past decade, a growing body of research has shown that reading and writing involve orthographic processing and phonological processing both in alphabetical and in nonalphabetical languages (Afonso and Alvarez 2011;Kandel et al 2009;Mousikou et al 2010;Qu et al 2011). Moreover, a longitudinal developmental study showed that both orthographical and phonological skills accounted for independent variance in later orthographic skills (Sprenger-Charolles et al 2003).…”
Section: Introductionmentioning
confidence: 99%